The evolution of institutional economics : agency, structure, and Darwinism in American institutionalism - Hodgson, Geoffrey Martin, 1946- (Economics as social theory., 2004)
This book charts the rise, fall and renewal of institutional economics in the critical, analytical and readable style that Hodgson's fans have come to know and love, and that a new generation of readers will surely come to appreciate.